Is Criticism Disloyal? American Jews' Attitudes toward Israel. Issue 1 (March 2022) - Wright, Graham; Saxe, Leonard; Wald, Kenneth D.
Abstract: To what extent is it possible for American Jews to maintain a deep emotional connection to Israel while criticizing the actions of the Israeli government? This long-debated question echoes earlier investigations of different forms of patriotism toward one's home country. Drawing on two 2019 surveys of American Jews, we find that, like Americans in general, Jewish liberals and conservatives express different forms of patriotism toward both Israel and America. Jewish conservatives tend to oppose criticism of Israel and America for any reason, while Jewish liberals view criticism as an important part of "caring" about both countries. Both forms of patriotism are positively associated with stronger emotional connections to the relevant country. These results suggest that emotional connection to Israel represents a form of social identification with Israel and that lower levels of connection to Israel among some American Jews are driven more by apathy than active criticism or hostility.